Design of parallel processing vertical climbing robot for autonomous bolt tightening of steel structure bolts - Chu, Timothy Scott; Chua, Alvin (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
A design of a vertical climbing robot is proposed for steel structure application which specializes in bolt tightening. It utilizes 2 main components, the robot positioning and bolt tightening mechanisms. The robot positioning mechanism allows the robot to move vertically along the steel column; while, the bolt tightening mechanism executes the bolt tightening sequence. The robot should be able to climb up steel I-beam columns, detect location of snug-tightened bolts, map the position of each bolt, and tighten the bolts. The research begins with the design for each component and defining its function and validation is done through simulation of the control process in PICOSOFT 6. The mechanical design of the robot compared to the CFs consists less components which allow quick and flexible installation as it can adjust to different column specifications. The simulation is able to show and execute the sequence of tasks executed such as climbing, sensing of bolts, mapping, and bolt tightening. The vertical climbing robot can execute the bolt tightening task similar to CFs, however the robot is integrated with parallel processing allowing it to be autonomous and consume less time to execute bolt tightening tasks. It maps out the bolts through the CHT algorithm together with the CAM shift method to accurately locate the position of the bolt and tighten the bolts successively with minimal human interaction. Since the paper offers a simulation of the process, further studies such as physical experimentation can be applied to further validate the application of the robot in construction.